Poland’s Aid to Ukraine Through the Lens of Responsibility to Protect (R2P) [version 1; peer review: 2 approved] - Agnieszka Bieńczyk-Missala (Stosunki Międzynarodowe)
This article analyzes Poland’s multifaceted response to the Russian aggression against Ukraine through the lens of the Responsibility to Protect (R2P) doctrine. It focuses on the often-overlooked role of neighbouring states in atrocity prevention and response, specifically exploring how Poland contributed under R2P Pillar II (international assistance and capacity-building) and Pillar III (timely and decisive response). The article addresses a research gap concerning the practical application of R2P by neighbouring states, which possess both proximity and strategic interest in regional stability but are rarely analyzed as primary actors within the R2P framework. The goal is to assess the extent to which Poland’s humanitarian, diplomatic, legal, and military measures aligned with R2P obligations and contributed to mitigating mass atrocity risks. The author investigates three central questions: what obligations do neighbouring states bear in preventing mass atrocities? Which R2P instruments did Poland apply? And how did it justify its policy? The study employs a narrative and content analysis of legal documents, government materials, multilateral resolutions, and NGO reports. Poland’s response included welcoming millions of refugees, providing medical and humanitarian aid, supporting international accountability mechanisms, and delivering significant military assistance. Poland also played a role in building international consensus on accountability and war crimes prosecution, including support for the ICC and the proposed special tribunal on aggression. By highlighting Poland’s engagement, this article contributes to a broader understanding of how states can operationalize R2P principles. It demonstrates that neighbouring countries, driven by both moral and legal obligations and strategic interest, can act as crucial agents in atrocity prevention and response, reaffirming the practical relevance of R2P in contemporary conflicts.